Energy solutions to improve production - Programa Alianza en Energía y Ambiente con la Región Andina (AEA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
Energy is everywhere, but the most valuable energy is found in nature and in people’s creativity to use it for their benefit. The Inter-American Institute for Cooperation on Agriculture (IICA), with the financial support of the Ministry for Foreign Affairs of Finland, implements 19 projects in Bolivia, Colombia, Ecuador and Peru in the frame of the Energy and Environment Partnership Programme with the Andean Region (EEP). The projects proved that it is indeed possible to apply technologies based on renewable energy sources to help rural populations gain energy autonomy. A number of these projects aim to improve production processes.